The Influence of Policy Implementation Dimensions on Service Effectiveness Mediated by Access to Health Services at Community Health Centers (Architecture Image Studies, 2026)
This study aims to examine and explain the influence of policy implementation dimensions on service effectiveness mediated by access to health services at the Kendari City Community Health Center. This study is an explanatory study with a quantitative approach and survey method. The study population was patients who visited the General Polyclinic of the Community Health Center in Kendari City during the study period with a sample of 391 respondents. Data were collected through a Likert-scale questionnaire, tested for validity and reliability, then analyzed using Structural Equation Modeling based on Partial Least Square (PLS) with the help of SmartPLS software version 4. The results showed that communication, resources, disposition, and bureaucratic structure had a positive and significant effect on both service effectiveness and access to health services. Access to health services was also proven to have a positive and significant effect on service effectiveness, although with a smaller coefficient compared to the direct influence of communication, resources, disposition, and bureaucratic structure. In addition, access to health services plays a significant partial mediator in the relationship between communication, resources, disposition, and bureaucratic structure on service effectiveness. This finding suggests that local governments and community health center (Puskesmas) managers should focus improvements in policy implementation not only on administrative compliance but also on increasing access to health services to achieve sustainable service effectiveness.